Statues and Democracy: The Political Dynamics of Urban Assemblage - Machin, Amanda (Theoria (Pietermaritzburg), 2025)
Although they often go unnoticed, the statues that stand in town squares and city parks around the world remain significant in contemporary societies. Statues are highly political artefacts that reflect and reproduce dominant sociopolitical narratives of the past and urban imaginaries of the present and can become the focus of celebration or controversy. This article argues that a statue forms part of an ‘urban assemblage’, comprised of a heterogeneous multiplicity of material objects, inscribed text, historical narratives, living bodies and emotional performances, that emerges through processes of depoliticisation and re-politicisation. Urban assemblages are stabilised to entrench particular social relations but can always be destabilised. Illustrating my arguments with the examples of the Emmeline Pankhurst statue in Manchester and the Edward Colston statue in Bristol, I discuss the movements around urban assemblages and the possibilities of democratic interventions in the city.